Interpreting Some Different Approaches to Teacher Education - Northfield, Jeff. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This paper describes a teacher education effort that developed conditions for teachers to be more effective learners about teaching and encouraged teachers' development of a personal understanding of educational issues. A group of teachers in one school established the Project To Enhance Effective Learning (PEEL) as an approach to encourage more active learning in their students. The teachers reflected on their day-to-day classroom experiences in the company of colleagues each week. The PEEL experience warrants close attention as an example of teacher education for a number of reasons: (1) It did not have a high cost structure; (2) teachers led the way in researching constructivist learning theories at the classroom level; (3) teachers learned from others with different discipline backgrounds; (4) teachers published accounts of their action research experiences for other teachers; and (5) problems with implementation of teaching methods become part of the research process. The paper reprints a model describing developmental stages in teachers' reflective judgement on the best way to teach. The paper concludes that preservice teacher education should incorporate more valid and extended school experience into educational programs. (Contains 11 references.) (JDD)
ERIC Note: Paper presented at the Annual Meeting of the National Association for Research in Science Teaching (Atlanta, GA, April 15-18, 1993).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Action Research; Cognitive Restructuring; Constructivism (Learning); Educational Change; Elementary Education; Faculty Development; Foreign Countries; Group Discussion; Higher Education; Inservice Teacher Education; Instruction; Preservice Teacher Education; Teacher Attitudes; Project to Enhance Effective Learn (Australia); Australia; Speeches/Meeting Papers; Reports, Descriptive